2020
DOI: 10.3389/fmicb.2020.00426
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Chicken Cathelicidin B1 Against Influenza A Virus

Abstract: Cathelicidins (CATHs) are host defense peptides (HDPs) that play an important role in the innate immune response against infections. Although multiple functions of cathelicidins have been described, including direct antimicrobial activity and several immunomodulatory effects on the host, relatively little is known about their antiviral activity. Therefore, in vitro antiviral activity of chicken cathelicidins and the underlying mechanism was investigated in this study against different influenza A virus (IAV) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In this study, we showed that APEC upregulates gene expression of CATH-B1 in macrophages but not of CATH-1, -2, -3. Recently, it was found by our group that CATH-B1 has strong antiviral activity against influenza A viruses in vitro [ 14 ]. In this study, the immunomodulatory effect of CATH-B1 on APEC-, LPS- or ODN-2006-activated chicken macrophages was explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we showed that APEC upregulates gene expression of CATH-B1 in macrophages but not of CATH-1, -2, -3. Recently, it was found by our group that CATH-B1 has strong antiviral activity against influenza A viruses in vitro [ 14 ]. In this study, the immunomodulatory effect of CATH-B1 on APEC-, LPS- or ODN-2006-activated chicken macrophages was explored.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in ovo administration of the all D-amino acid enantiomer of CATH-2 (D-CATH-2) at embryonic day 18 resulted in a protective effect against avian pathogenic E. coli (APEC) infection up to 7 days after hatch [ 13 ]. However, less is known about the activities of CATH-B1, which means that it is challenging to properly compare functionalities and activities [ 14 ]. When comparing expression patterns, one clear difference between CATH-1, -2, -3 and CATH-B1 is apparent: using immunostaining and mass spectrometry CATH-1, -2, -3 were detected in heterophils [ 15 ], while CATH-B1 was shown to be produced by epithelial cells in the bursa of Fabricius, although an extended description of CATH-B1 protein expression among cells/tissues was not described [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study pertaining to this subject of beetle defensin revealed the anticancer effect of a combination of this gene with synthetic peptides on certain cancers (56). Peng et al (17)(18) concluded that chicken cathelicidin-2 and -B1 have both antibacterial and immunomodulatory roles when they incubated with chicken macrophages cell line infected by pathogenic E. coli through neutralisation of certain bacterium and decreases in ammation response.…”
Section: Discussionmentioning
confidence: 99%
“…Considering other peptides, gene duplication leads to the formation of mature peptides CATH-1 and CATH-3 having about 70% similar sequence (5)(6)(7).However, only their antibacterial properties have been extensively studied in majority of research (8)(9)(10)(11)(12). Several studies have been investigated the antimicrobial and immunomodulatory potentialities of chicken cathelicidin-2 through activating toll like receptor-2 and neutralization of LPS (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has also been determined that defensins, such as αand β-defensins, have antiviral activity against IAV (Doss et al, 2009). Extensive studies have been carried out on chicken cathelicidins, which have been found to exhibit various activities (Peng et al, 2020). In addition to broad-spectrum antibacterial activity, they also possessed immunomodulatory functions; hence, they may be able to activate phagocytosis, neutralize LPS-induced immune responses and improve DNA-induced TLR21 activation (Veldhuizen et al, 2013;Coorens et al, 2015;Coorens et al, 2017, Peng et al, 2020.…”
Section: Discussionmentioning
confidence: 99%